PENGARUH KUALITAS PELAYANAN DAN HARGA TERHADAP KEPUTUSAN PEMBELIAN PADA BRAND JSP KIDS MDS DEPOK TOWN SQUARE - Agung Tri Putranto; Sigit Purnomo (Sekolah Menengah Kejuruan (SMK) Pustek, 2022)
This study aims to determine how much service quality and price affect the purchasing decision simultaneously at JSP Kids MDS Depok Town Square Brand. This type of research is an associative research using a quantitative approach. The sampling technique used in this study is simple random sampling, using a sample of 99 respondents. Data analysis is a research instrument testing that is validity test, reliability test, classical assumption test. Descriptive analysis and research verification are analysis of respondent characteristics, descriptive analysis of respondents' assessment of qualitative variables, verification analysis (quantitative) namely linear regression analysis, correlation coefficient analysis, coefficient of determination analysis, and hypothesis testing both partially and simultaneously. The results of this study are the quality of service has a positive and significant effect on purchasing decisions with the regression equation Y= 15,767 + 0.502 X1. Price has a positive and significant effect on purchasing decisions with the regression equation Y= 10,738 + 0.635 X2. Service quality and price simultaneously have a positive and significant effect on purchasing decisions with the regression equation Y = 7.843 + 0.116X1 + 0.586X2. This means that there is a positive and significant influence simultaneously between service quality and price on purchasing decisions on the JSP KIDS MDS Depok Town Square brand.